Study on Sustainable Agriculture in West Papua: in terms of the Aspects of Plant Productivity and Land Use Change - Kati Syamsudin Kadang Tola; Samsul Bachri (Agrotek, 2023)
Land availability and crop productivity are important in realizing sustainable agriculture in West Papua. This study aims to provide an overview of agricultural development in West Papua in terms of agricultural aspects and changes in land use. This research is descriptive-analytic in nature, using population data for the period 2003-2018, data on paddy rice, cassava, sweet potato, dry-field rice and corn. Land use data for the 1996-2019 period and potential agricultural land cover for 2021. The results obtained are an average population growth rate of 3.4 percent. The conditions of lowland rice, cassava and sweet potato crops for the 2004-2018 period are as follows: The average productivity of lowland rice is 3.72 tonnes/ha or 37.2 quintals/ha. Cassava production was very fluctuating, which was obtained that the average productivity of cassava was 12.03 tons/ha or 120 quintals/ha. Sweet potato crop productivity decreased in 2018 with an average sweet potato productivity of 11.11 tons/ha or 111.1 quintals/ha. The condition of dryland paddy and maize for the 2003-2017 period showed that the production and harvested area of upland paddy tended to decrease every year with an average dryland paddy productivity of 2.86 tons/ha or 28.6 quintals/ha while corn productivity continued to increase until 2017 with the average productivity is 1.78 tonnes/ha or 17.8 quintals/ha. Aspects of changes in land use in the agricultural sector for the period 1996-2019 obtained that dryland agriculture and mixed dryland agriculture tended to decrease.